2009
DOI: 10.1063/1.3177352
|View full text |Cite
|
Sign up to set email alerts
|

On the dynamics of axisymmetric turbulent separating/reattaching flows

Abstract: The authors hypothesized that both narcissism and high selfesteem are associated with positive self-views but each is associated with positivity in different domains of the self. Narcissists perceive themselves as better than average on traits reflecting an agentic orientation (e.g., intellectual skills, extraversion) but not on those reflecting a communal orientation (e.g., agreeableness, morality). In contrast, high-self-esteem individuals perceive themselves as better than average both on agentic and commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 77 publications
8
73
1
Order By: Relevance
“…A dedicated ZDES simulation (Deck 2005(Deck , 2012) is performed building on ample experience with applying ZDES to axisymmetric base flows (e.g., Deck and Thorigny 2007;Weiss et al 2009;Weiss and Deck 2011). ZDES is closely related to the classical detached eddy simulation (DES).…”
Section: Zonal Detached Eddy Simulation (Zdes)mentioning
confidence: 99%
“…A dedicated ZDES simulation (Deck 2005(Deck , 2012) is performed building on ample experience with applying ZDES to axisymmetric base flows (e.g., Deck and Thorigny 2007;Weiss et al 2009;Weiss and Deck 2011). ZDES is closely related to the classical detached eddy simulation (DES).…”
Section: Zonal Detached Eddy Simulation (Zdes)mentioning
confidence: 99%
“…In these computations, the grids were noticeably ¦ner and it was shown that azimuthal resolution had a dramatic e¨ect on the results. An accuracy of about 15% was obtained with 2.5 • between each plane [2] and around 5% [12] with 1.5 • (5 • was retained for the present study). The greater azimuthal resolution probably enhances the mixing thus leading to a greater disorganization and dissipation of the coherent vortices.…”
Section: Pressure Fluctuations Levelsmentioning
confidence: 95%
“…The vortices must be too coherent and their three-dimensionality nature underevaluated. The DES simulations [2,12] are Figure 4 Longitudinal distribution of the unsteady pressure coe©cient: 1 ¡ PANS simulation; and 2 ¡ experiments found to give a better estimation of the §uctuation levels on the same con¦gu-ration. In these computations, the grids were noticeably ¦ner and it was shown that azimuthal resolution had a dramatic e¨ect on the results.…”
Section: Pressure Fluctuations Levelsmentioning
confidence: 99%
“…This is rather coarse, but allows keeping computational costs to within an industrially acceptable level. Results are compared to the available experimental data [13,14] and to ZDES calculations [15,16] with differents grids listed in the Table 2. Figure 8 represents a snapshot of the instantaneous flow field, showing the coherent structures in the recirculation area downstream of the backward facing step.…”
Section: Axisymmetric Backward Facing Stepmentioning
confidence: 99%